2003
DOI: 10.1046/j.1365-2591.2003.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of the current status of tooth whitening with the walking bleach technique

Abstract: Internal bleaching procedures such as the walking bleach technique can be used for whitening of discoloured root-filled teeth. The walking bleach technique is performed by application of a paste consisting of sodium perborate-(tetrahydrate) and distilled water (3% H2O2), respectively, in the pulp chamber. Following a critical review of the scientific literature, heating of the mixture is contra-indicated as the risk of external cervical resorption and the formation of chemical radicals is increased by applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
210
0
60

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(273 citation statements)
references
References 122 publications
3
210
0
60
Order By: Relevance
“…6,29,30 These conditions were augmented when the in-office bleaching technique, which uses bleach at a higher concentration, was performed. 31,32 As a result, a 24-hour to one-month waiting period after bleaching has been recommended before performing restorative procedures. The decrease in bond strength and reduction of the adhesive system interaction in bleached teeth are attributed to the presence of residual oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…6,29,30 These conditions were augmented when the in-office bleaching technique, which uses bleach at a higher concentration, was performed. 31,32 As a result, a 24-hour to one-month waiting period after bleaching has been recommended before performing restorative procedures. The decrease in bond strength and reduction of the adhesive system interaction in bleached teeth are attributed to the presence of residual oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…In group 3, the highly concentrated hydrogen peroxide gel was applied 5 times for 30 min imitating chairside in-office bleaching treatment. For simulation of the walking-bleach technique (group 4) the mixture of sodium perborate and distilled water was applied on dentine surfaces as recommended by Attin et al [1]. Between the treatments and during the post-treatment observation period, the samples were stored in artificial saliva and exposed alternately to dark conditions or daylight to simulate clinical conditions in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds to the fact that clinically visible damage due to vital bleaching has not been described in the literature, although it is reported that bleaching non-vital teeth involves the risk of developing external cervical resorption. [1][2] Despite the fact that vital bleaching is not thought to create macroscopically visible defects, some studies have exhibited micro structural changes in dental hard tissue induced by bleaching agents, especially when bleaching agents are applied in high concentrations. 3 In addition, hydrogen and carbamide peroxide, which are commonly used bleaching agents, affect the bonding of enamel and dentin tissue when restorations are applied directly after bleaching treatment.…”
Section: Introductionmentioning
confidence: 99%